Activation modes in biocatalytic radical cyclization reactions. (1st March 2021) - Ye, Yuxuan; Fu, Haigen; Hyster, Todd K
Abstract: Radical cyclizations are essential reactions in the biosynthesis of secondary metabolites and the chemical synthesis of societally valuable molecules. In this review, we highlight the general mechanisms utilized in biocatalytic radical cyclizations. We specifically highlight cytochrome P450 monooxygenases (P450s) involved in the biosynthesis of mycocyclosin and vancomycin, nonheme iron- and α-ketoglutarate-dependent dioxygenases (Fe/αKGDs) used in the biosynthesis of kainic acid, scopolamine, and isopenicillin N, and radical S -adenosylmethionine (SAM) enzymes that facilitate the biosynthesis of oxetanocin A, menaquinone, and F420. Beyond natural mechanisms, we also examine repurposed flavin-dependent "ene"-reductases (ERED) for non-natural radical cyclization. Overall, these general mechanisms underscore the opportunity for enzymes to augment and enhance the synthesis of complex molecules using radical mechanisms.